Wunder auf dem Weg durch die Wüste. Israels Verwandlung zum Ort der Gegenwart JHWHs in Ps 114 - Siquans, Agnethe 1971- (2012)
Psalm 114 tells the story of Israel’s transformation into YHWH’s sanctuary, the place of his presence in the world. Time and especially space are also transformed: What happened once in the past, may happen time and again. As for space, the land is an important feature, but YHWH’s presence is bound to Israel, his people. Strikingly - especially in comparison to some biblical intertexts -, the temple or Jerusalem are not mentioned in the psalm. The sanctuary is where Israel is, not only within the land, but also in the diaspora.